Labyrinthectomy after Cochlear Implantation: A Case of a Novel Approach for Vertigo Control. (31st March 2019) - Todt, I.; Wilms, K.; Sudhoff, H.
Abstract : Vertigo control in cases of Ménière disease and deafness can be achieved by labyrinthectomy before or as a single-stage procedure during cochlear implantation. The aim was to describe a case in which a labyrinthectomy was performed after cochlear implantation. The scar tissue was removed from the electrode cable, and the receiver was removed from the periostal pocket and placed out without electrode dislocation. Labyrinthectomy was performed after securing the electrode at the external canal. The patient disclaimed after three months no disabling vertigo. Intraoperatively, the electrode was not dislocated. A labyrinthectomy can be performed even after cochlear implantation to treat vertigo.